Current status of the oak gallwasp (Hymenoptera: Cynipidae: Cynipini) fauna of the Eastern Palaearctic and Oriental Regions - Pénzes, Zsolt; Tang, Chang-Ti; Stone, Graham N.; Nicholls, James A.; Schwéger, Szabina; Bozsó, Miklós; Melika, George (Zootaxa, 2018)
Cynipid gallwasps comprise 1364 species worldwide, predominantly in temperate regions of the Holarctic. The vast majority of recorded species are from the Nearctic and the Western Palaearctic, both of which are long-standing centers of research on the taxonomy and biology of this group. In contrast, the Eastern Palaearctic and the Oriental Region faunas are much less studied, but potentially extremely rich. Previously recorded species richness of cynipid groups in the Eastern Palaearctic and Oriental regions probably represents a significant underestimate. This is particularly marked for gallwasps associated with oaks (tribe Cynipini), as has been shown by recent works, which describe many new species galling oaks in the subgenera Quercus and Cyclobalanopsis and plants of the other Fagaceae genera (Castanopsis, Lithocarpus and Castanea). In the present paper, we summarise the current knowledge of oak gallwasps in the regions that extend from Pakistan, through Nepal and China to Japan and south to Indonesia, and list a total of 97 species of Cynipini from the area.